First integrated core-edge fluid simulation of ITER’s Limiter–Divertor transition with SolEdge-HDG - M. Scotto d’Abusco; I. Kudashev; G. Giorgiani; A. Glasser-Medvedeva; F. Schwander; E. Serre; J. Bucalossi; H. Bufferand; G. Ciraolo; P. Tamain (Nuclear Materials and Energy)
This work explores the Limiter–Divertor transition (L–D) during the current ramp-up of ITER’s Q = 10 baseline plasma scenario at various central line-integrated density nli values. The analysis, based on transport simulations performed with the latest version of SoleEdge-HDG, focuses on the time evolution of heat and ion particle fluxes, revealing regions of elevated temperature on the inner wall and plasma-facing components (PFCs) despite moderate loads. The investigation also delves into the effects of perpendicular convection flux terms on density build-up, comparing different formulations and their interplay with auxiliary heating sources. Furthermore, the paper shows the impact of taking into account the evolution of the parallel neutral momentum on plasma and neutral density at the targets in the context of an ITER steady-state scenario.